Standardization of Fertilizer Application through Drip System as Compared to Conventional Method of Basin Fertigation in Orange - Kumar, Pramod; Sinha, Anuradha; Swapnil; Lata, Suman; Singh, Digvijay (International Journal of Economic Plants, 2021)
Orange (Citrus sinensis) is important tropical or sub-tropical fruit crop which belong to family Rutaceae having chromosome number 2n= 2x=18 which contains vitamin C, fiber and several phytochemical compounds. Citrus sinensis has evergreen and perennial in nature. Because of perennial nature it requires water and nutrients all over the year for their greater yield and productivity. A study was undertaken to determine the quantity of fertilizer application through drip system as compared to conventional method of basin fertigation in orange during kharif season of 2014, on Nagpur variety of orange at Agricultural Engineering at ZRS, Chianki, Palamau district in Jharkhand, India. There were total four treatments combination was applied namely Treatment 1- V volume of water by drip +100% fertilizer (N), Treatment 2- V volume of water by drip+80% fertilizer (N), Treatment 3- V volume of water by drip+60% fertilizer (N) and Treatment 4- V volume of water by basin irrigation+100% fertilizer by soil incorporation (N) and it was found that 100% application of fertilizer through drip system show best result for all the observation such as maximum FUE (0.0059 q ha-1 INR-1), plant girth (28.4 cm) and plant spread (EW-290.1, NS-263), WUE (0.56 q ha-1 cm-1), fruit weight (79%), fruit yield (38.4 q ha-1), net seasonal income (99866) and maximum Net B.C ratio. This may be due to vegetative growth, fruit yield, fruit weight and quality of fruit which fetches more lucre in market as compared to conventional method of basin fertigation which is useful for farmers.